(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the theoretical and methodological foundations and practical possibilities of managing inclusive education and rehabilitation processes based on an integrative approach. Inclusive education is interpreted as a complex pedagogical system that ensures the full integration of children with special educational needs into the general educational environment. The issues of the continuity of educational and rehabilitation services, multidisciplinary cooperation, the development of individual educational programs and the introduction of monitoring mechanisms are covered.